Creatine Supplementation and Akt/mTOR Pathway: Unraveling the Connection for Optimal Muscle Performance - Leite, Mateus O; Knifis, Franz W; Machado, Marco (Journal of Sports Medicine and Therapy, 2023)
This review paper investigates the relationship between creatine supplementation and the Akt/mTOR pathway, focusing on their impact on muscle performance. The Akt/mTOR pathway is a crucial signaling pathway that regulates muscle protein synthesis and hypertrophy in response to growth factors, nutrients, and mechanical stimuli. Recent evidence suggests that creatine supplementation can influence anabolic signaling pathways, including the phosphorylation of p70S6K, a downstream target of mTOR, leading to enhanced activation of the Akt/mTOR pathway. Additionally, creatine supplementation has been shown to increase intramuscular creatine and phosphocreatine levels, improving ATP availability during exercise and enhancing high-intensity muscle contractions. Understanding the complex regulatory mechanisms of the Akt/mTOR pathway is vital for optimizing muscle performance, as dysregulated signaling can hinder muscle protein synthesis and hypertrophic responses. This review highlights the potential of creatine supplementation to modulate the Akt/mTOR pathway, offering insights into its mechanisms and implications for muscle performance enhancement. By unraveling this connection, researchers and practitioners can develop targeted strategies to maximize muscle performance and promote adaptive responses in various exercise and athletic contexts.